Caesarean Scar Pregnancy: A Case Report - Vilius Rudaitis; Gailė Maldutytė; Jūratė Brazauskienė; Mykolas Pavlauskas; Dileta Valančienė (Acta Medica Lituanica, 2022)
Caesarean scar pregnancy is a potentially life-threatening gynaecological condition, becoming more common due to steadily increasing rate of caesarean sections worldwide. More than one-third of women presenting with caesarean scar pregnancy are asymptomatic, but over the time if left untreated this condition can lead to the uterine rupture and massive maternal haemorrhage. Therefore it is necessary to diagnose and manage caesarean scar pregnancies properly at the beginning of the first trimester. We present the case of woman with three previous caesarean sections, who was diagnosed with complicated caesarean scar pregnancy and then successfully managed using surgical intervention.